COMPARATIVE STUDY OF FINE NEEDLE ASPIRATION CYTOLOGY AND HISTOPATHOLOGY IN GRADING BREAST CARCINOMA - DR.VIJAYALAXMI.S.PATIL; DR.R.M.POTEKAR; DR.B.R.YELIKAR; DR.M.H.KARIGOUDAR (International Journal of Pharma and Bio Sciences, 2014)
Grading of tumors in Fine Needle Aspiration Cytology (FNAC) is a useful tool for selecting therapy and prognosis in breast carcinoma patients. A total of 38 patients of Infiltrating ductal carcinoma of breast who underwent FNAC and mastectomy were cytologically and histologically graded (employing Taniguchi’s cytological grading system and Scarff Bloom Richardson grading method respectively).Statistical analysis was done using ‘Z’ test and ‘χ2’ test. The lymph nodes were also studied for detection of metastasis. Total concordance between Cytological grade(CG) and Histological grade(HG) was seen in 78.95% of cases and Positive correlation between the two grading systems was also noted. Lymph node metastasis was seen in 52.63% of cases which was maximum in grade III cases. Cytological grading of breast carcinoma correlates well with histological grading and it may be useful in the prognostic evaluation of the cases without additional morbidity or expense to the patient.